(untitled) (Construction Economics and Building, 2020)
The quest for smart cities and development has been on the increase among infrastructural development stakeholders, including clients, government agencies responsible for the management of infrastructures, construction professionals, sponsors, and financiers of these projects. However, studies around the world have shown that less attention is being paid by these stakeholders to various indices and measures of smart cities. These measures and indices, known as drivers, are smart environment, smart economy, smart people, smart governance, smart mobility, and smart living. Using these drivers and their indicators, a multiple-choice questionnaire was designed in line with existing and relevant literature materials in the subject area. These questionnaires were administered on construction professionals with relevant and adequate knowledge of smart construction. Smart environment was found to be a major driver of a smart city while smart people, smart governance and smart living are also key to the achievement of the goals and objectives of the concept. The developed key smart city drivers are a workable, adaptable and efficient city design mechanism and it will be useful for city planners, statutory agencies as well other stakeholders in the development of smart cities.